Impact of Service Quality Dimensions on Customer Satisfaction in Commercial Bank - Mishra, Udgam (Rupantaran: A Multidisciplinary Journal, 2020)
The ever-changing behavior of customer has indulged bank and financial institution have a sincere look at its service quality. Providing quality service ensures competitiveness and simultaneously optimizing the level of customer satisfaction. This paper examines the impact of Service Quality Dimensions on customer satisfaction. This paper examines the impact of tangibility, responsiveness, reliability, assurance and empathy on customer satisfaction in banks of Biratnagar. A sample of 127 account holders were randomly selected and date were analyzed through SPSS 26.0. Descriptive statistics, Factor analysis and Multiple regression analysis were used to evaluate the impact of SERVQUAL model on satisfaction. The findings from the paper indicate that empathy and assurance have most significant influence in satisfaction followed by reliability and responsiveness whereas tangibility has negative and no significant relationship with satisfaction.